Characteristics of white spot lesions associated with orthodontic treatment: a review - Consoli Senno, Michella Vicenza (2023)
Introduction: The purpose of this literature review is to provide scientific evidence on the characteristics of white spot lesions (WSL) during orthodontic treatment, their incidence, prevalence, risk factors related to their development, progression, and regression, as well as explain the most used diagnostic methods. Materials and methods: An exhaustive search was carried out in the databases of Pubmed, Scopus, Science Direct and Embase up to the date of November 30, 2022. Cross-sectional studies that evaluated white spot lesions before and after orthodontic treatments were included. Two researchers carefully selected the articles evaluated and analyzed different key topics on the subject. Results: It was found that the prevalence and incidence of white spots during orthodontic treatment varies widely depending on the diagnostic method used, the type of orthodontic technique used and the time of orthodontic treatment. The incidence of white spot lesions is highest in patients treated with conventional braces, followed by those who used self-ligating braces, and was lowest in patients who used aligners. The most affected teeth are the upper lateral incisors and upper maxillary canines at the level of the gingival third. Conclusions: The incidence of white spots is associated with orthodontic treatment, being closely related to the treatment technique used and the treatment time. There is a regression of the LMB during the first year after removal of the appliance.